2023
DOI: 10.1021/acs.langmuir.3c00028
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Regulation of the Microstructure and Acidity of HZSM-5/MCM-41 for Efficient Catalytic Cracking of n-Decane

Abstract: Alkane catalytic cracking is regarded as one of the most significant processes for light olefin production; however, it suffers from serve catalyst deactivation due to coke formation. Herein, HZSM-5/MCM-41 composites with different Si/Al2 ratios were first prepared by the hydrothermal method. The physicochemical properties of the prepared catalysts were analyzed by a series of bulk and surface characterization methods, and the catalytic performance was tested in n-decane catalytic cracking. It was found that H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The method for calculating the amount of BAS and LAS is also reported in literature. 21,23 Single-pulse 27 Al, 29 Si, and 71 Ga solid-state MAS NMR measurements were conducted on a JEOL JNM ECZ600R NMR spectrometer. The relaxation delay is 1.0000 s, pulse time is 0.1 μs, and repetition time is 1.00524 s. The MAS frequency is 15.002 kHz and spectrometer frequency is 156.39 MHz.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method for calculating the amount of BAS and LAS is also reported in literature. 21,23 Single-pulse 27 Al, 29 Si, and 71 Ga solid-state MAS NMR measurements were conducted on a JEOL JNM ECZ600R NMR spectrometer. The relaxation delay is 1.0000 s, pulse time is 0.1 μs, and repetition time is 1.00524 s. The MAS frequency is 15.002 kHz and spectrometer frequency is 156.39 MHz.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…20 HZSM-5 is a promising catalyst due to its suitable microporous structure and acid properties as well as strong resistance to coke deactivation. 21 However, the aromatic selectivity of the aromatization reaction catalyzed by HZSM-5 is low and easy to deactivate. 22 It has been reported that HZSM-5 modified with metals such as Ga, 23 Zn, 24,25 Re, 26 In 27 can further improve the dehydrogenation performance of the light alkane aromatization reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, adverse effects such as plasma protein adsorption may occur quickly during ECMO treatment, which would affect the efficiency of the ECMO membrane, and even lead to platelet adhesion and further clotting. [6][7][8] Due to the limitations of the preparation methods of the traditional ECMO commercial materials, PMP and PP, many studies focus on preparing anticoagulant coatings with heparin, 9 albumin, 10 silicone 11 and cross-linked polyvinyl alcohol 12 on the surface to improve the blood compatibility. However, protein adsorption resulting from the nature of the hydrophobic matrix would still affect the efficiency of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The structurereactivity analysis reveals that the conversion of n-decane, light olefin selectivity, and deactivation rate are determined by the total acid density and diffusion rate, which synergistically affect the catalyst performance. 25 In another research investigates the separate pyrolysis of corn stalk (CS) and polypropylene (PP) as well as their co-pyrolysis over Zn-Al co-modified MCM-41 catalysts for the production of aromatics. The catalysts were found to significantly influence the product contents and composition.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that HZSM‐5/MCM‐41 composites exhibit higher selectivity to light olefins and lower deactivation rates than parent HZSM‐5, and further improvement is achieved by extruding the composites with γ‐Al 2 O 3 . The structure‐reactivity analysis reveals that the conversion of n‐decane, light olefin selectivity, and deactivation rate are determined by the total acid density and diffusion rate, which synergistically affect the catalyst performance 25 . In another research investigates the separate pyrolysis of corn stalk (CS) and polypropylene (PP) as well as their co‐pyrolysis over Zn–Al co‐modified MCM‐41 catalysts for the production of aromatics.…”
Section: Introductionmentioning
confidence: 99%